Antrochoanal polyp mimicking juvenile nasoangiofibroma - Muhammed, NA; Mohamad, I; Abdullah, B (Bangladesh Journal of Medical Science, 2013)
Antrochoanal polyp is a benign lesion, usually arising from the maxillary sinus extending posteriorly into the nasopharynx. Typically it presents as a unilateral nasal obstruction with mucopus rhinorrhea, sleep disturbance, postnasal drip, and mouth breathers. Epistaxis is an extremely rare complaint. Unilateral nasal mass presenting in a teenage boy will increase the suspicion of juvenile nasoangiofibroma. We report a teenage with extensive unilateral nasal mass with such presentation, which later turned out to be antrochoanal polyp. DOI: http://dx.doi.org/10.3329/bjms.v12i4.16664 Bangladesh Journal of Medical Science Vol. 12 No. 04 October 13 Page 432-434